Multicomponent Reactions Accelerated by Aqueous Micelles - Paprocki, Daniel; Madej, Arleta; Koszelewski, Dominik; Brodzka, Anna; Ostaszewski, Ryszard (Frontiers in Chemistry, 2018)
Multicomponent reactions are powerful synthetic tools for the efficient creation of complex organic molecules in an one-pot one-step fashion. Moreover, the amount of solvents and energy needed for separation and purification of intermediates is significantly reduced what is beneficial from the green chemistry issues point of view. This review highlights the development of multicomponent reactions conducted using aqueous micelles systems during the last two decades.